ANALYZING EFL UNIVERSITY STUDENTS’ CAPITALIZATION AND PUNCTUATION ACCURACY IN ACADEMIC WRITING - Nurhalimah Siregar; Nurmayana; Syamsul Bahri; Fatin Nadifa Tarigan (English Study Program University of Pasir Pengaraian, 2026)
Writing is a crucial skill in English that requires accuracy in using capitalization and punctuation to convey meaning effectively. This study aims to analyze EFL university students' capitalization and punctuation accuracy in academic writing. The research employed a qualitative descriptive method. The data were collected from the academic writing of first semester students at Universitas Pembinaan Masyarakat Indonesia Medan and analyzed using an error analysis approach. The findings indicate that students still experience difficulties in applying appropriate rules. The highest correct usage was found in periods (80 occurrences) and commas (73 occurrences), while the use of exclamation marks (4 occurrences) and question marks (3 occurrences) was relatively low. Errors were also frequently identified in the capitalization of proper nouns (18 occurrences) and sentence beginnings (87 occurrences). In addition, students tended to rely on simple sentence structures, which limited the variety of punctuation used.Overall, students’ accuracy is categorized at a moderate level. Therefore, more focused instruction and practice are recommended to improve students’ academic writing skills.